On the Internet of things drivers: A perception from SMEs in recent time - Adenekan, Tobiloba Adedoyin; Musibau, Hammed Oluwaseyi; Musibau, Hammed Oluwaseyi (Indonesian Journal Of Business And Economics, 2021)
The advent of information technology and Industry 4.0 has changed business practices such that organization rely more on internet of things to achieve effectiveness and efficiency. Hence, SMEs are becoming more aware of the importance of IoT in business. However, a lack of knowledge about its potential benefits easiness to adopt and technology anxiety mitigates some SMEs to invest in IoT. Hence, this study seeks to examine the determinants of IoT adoption in SMEs in Nigeria using Multiple Regression Analysis. Findings revealed that positive and significant effect of perceived ease of use, and perceived usefulness, while technology anxiety revealed a negative and significant impact on IoT adoption. Hence, IoT applications providers should focus on making the device easily accessible, convenient, and effortless. They should make way for communication flow with the users to reduce their anxiety.